2020
DOI: 10.1167/iovs.61.8.45
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Melatonin Levels Found in Young Myopic Adults Are Not Attributable to a Shift in Circadian Phase

Abstract: To evaluate the relationship between refractive error, circadian phase, and melatonin with consideration of prior light exposure, physical activity, and sleep. METHODS. Healthy young myopic (spherical equivalent refraction [SER] ≤−0.50DS) and emmetropic adults underwent noncycloplegic autorefraction and axial length (AL) measures. Objective measurements of light exposure, physical activity, and sleep were captured across 7 days by wrist-worn Actiwatch-2 devices. Questionnaires assessed sleep quality and chrono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 90 publications
3
50
2
Order By: Relevance
“…It should be considered that dopamine and melatonin circadian cycles oscillate in antiphase in the central nervous system [140], including the retina [141]. In this sense, recent studies showed that melatonin levels in body fluids such as serum and saliva were elevated in myopic subjects compared to emmetropes ones [142,143], but they were reduced in urine [144]. In accordance with the above, dopamine levels were also reduced in the serum of these myopic subjects [142].…”
Section: Myopiamentioning
confidence: 60%
“…It should be considered that dopamine and melatonin circadian cycles oscillate in antiphase in the central nervous system [140], including the retina [141]. In this sense, recent studies showed that melatonin levels in body fluids such as serum and saliva were elevated in myopic subjects compared to emmetropes ones [142,143], but they were reduced in urine [144]. In accordance with the above, dopamine levels were also reduced in the serum of these myopic subjects [142].…”
Section: Myopiamentioning
confidence: 60%
“… 263 More recently, this group reported that circadian rhythms in melatonin levels were not altered in myopes as compared with emmetropes. 265 In contrast, a more recent paper reported that melatonin levels were lower, and that there were phase shifts in rhythms. 266 At this stage, it is not clear whether these observations suggest a role for circadian rhythms, or whether the changes in melatonin levels are secondary to changes in dopamine metabolism.…”
Section: Other Risk Factors For Myopiamentioning
confidence: 93%
“…As previously reviewed, the measurement of melatonin in body fluids prior to the development of the first radioimmunoassays, was very difficult because of the extremely low daytime levels 9 . In the late 1970s, the power of mass spectrometry was applied to the field, first by Al Lewy and colleagues, 10 and subsequently by other groups 11,12 . These methods have both the sensitivity and specificity to be the gold standards for melatonin measurement.…”
Section: Figurementioning
confidence: 99%